’n Kontekstuele uitleg van Psalm 110 binne sy historiese raamwerk - J. J. de Bruyn; D. J. Human (In die Skriflig, 2006)
A contextual exegesis of Psalm 110 in its historical frame- work Psalm 110 is the psalm that is most revered to in the New Testament. The question can be asked whether the New Testament is the only key to the understanding of Psalm 110. Naturally, the exegetic model that one uses will have an influence on our understanding of the Psalm. The question that will be observed in this article is whether there can be another figure, in addition to Jesus Christ, that can be a priest from the order of Melchizedek. If so, that can shed an alternative light on Psalm 110 from that of the New Testament.